2002
DOI: 10.1292/jvms.64.445
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of Continuously Seropositive Population against Borna Disease Virus in Misaki Feral Horses, a Japanese Strain: A Four-Year Follow-Up Study from 1998 to 2001.

Abstract: ABSTRACT. Borna disease virus (BDV)-specific antibodies were monitored in Misaki feral horses annually for 4 years using an electrochemiluminescence immunoassay (ECLIA). Among 130 horses examined, 35 (26.9%) with an ECLIA count above 1000 once or more were judged as BDV seropositive. Throughout the study period, p24 antibodies were more frequent than p40 antibodies in almost all positive animals. Among the 35 seropositive horses, the ECLIA count was consistently high in 12 cases. Eleven horses seroconverted fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
5
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 11 publications
4
5
0
Order By: Relevance
“…This fits into our results of a striking difference (15 fold) of the BDV prevalence in thoroughbred vs. in Giara wild horses (38.2 % vs. 2.7 %), a population of horses that live freely in the central area of Sardinia island. A comparable prevalence like in thoroughbred had also been reported from the Misaki feral horse population (Inoue et al, 2002) in Japan, based on other infection markers.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…This fits into our results of a striking difference (15 fold) of the BDV prevalence in thoroughbred vs. in Giara wild horses (38.2 % vs. 2.7 %), a population of horses that live freely in the central area of Sardinia island. A comparable prevalence like in thoroughbred had also been reported from the Misaki feral horse population (Inoue et al, 2002) in Japan, based on other infection markers.…”
Section: Discussionsupporting
confidence: 80%
“…Furthermore, mounting evidence indicates that BDV infection occurs in humans and that it may be related to neuropsychiatric diseases. BDV infection in horses is endemic in Central Europe and apparently in Asia (Inoue et al, 2002). In Italy, BDV infection is currently regarded as an exotic disease in horses, and extensive serological investigations have been never performed.…”
Section: Introductionmentioning
confidence: 99%
“…Previous data indicated that the BDV P antibody was found in 20.3% of Holstein cows by Western blot analysis in Hokkaido [10]. Although BDV's natural reservoir(s) or vector(s) has not yet been identified, our data, together with previous studies [10,14], suggests that a follow-up study with area isolated cattle could be important for exploring the natural reservoir or vector of this virus.…”
supporting
confidence: 55%
“…In Kyushu, the southernmost main island of Japan, BDV infection and transmission were well documented in the Toimisaki herd of Japanese feral horses [14]. Inoue et al revealed that 26.9% of Misaki feral horses are seropositive for BDV after four years of surveillance using an electrochemiluminescence immunoassay.…”
mentioning
confidence: 99%
“…However, the conflicting results regarding BDV infection cannot be attributed only to geographic factors. It has been reported that BDV is not associated with psychiatric patients in Kyushu island in Japan, a known endemic area of BDV infection 8,42,49. However, there have been two BDV-positive reports in Brazil, which has not been known to be an endemic BDV infection area 23,24.…”
Section: Discussionmentioning
confidence: 96%